RPL22L1 induction in colorectal cancer is associated with poor prognosis and 5-FU resistance. - Shuyun Rao; Suraj Peri; Jens Hoffmann; Kathy Q Cai; Bryan Harris; Michele Rhodes; Denise C Connolly; Joseph R Testa; David L Wiest (PLoS ONE, 2019)
We have previously demonstrated that loss of the tumor suppressive activity of ribosomal protein (RP) RPL22 predisposes to development of leukemia in mouse models and aggressive disease in human patients; however, the role of RPL22 in solid tumors, specifically colorectal cancer (CRC), had not been explored. We report here that RPL22 is either deleted or mutated in 36% of CRC and provide new insights into its mechanism of action. Indeed, Rpl22 inactivation causes the induction of its highly homologous paralog, RPL22L1, which serves as a driver of cell proliferation and anchorage-independent growth in CRC cells. Moreover, RPL22L1 protein is highly expressed in patient CRC samples and correlates with poor survival. Interestingly, the association of high RPL22L1 expression with poor prognosis appears to be linked to resistance to 5-Fluorouracil, which is a core component of most CRC therapeutic regimens. Indeed, in an avatar trial, we found that human CRC samples that were unresponsive to 5-Fluorouracil in patient-derived xenografts exhibited elevated expression levels of RPL22L1. This link between RPL22L1 induction and 5-Fluorouracil resistance appears to be causal, because ectopic expression or knockdown of RPL22L1 in cell lines increases and decreases 5-Fluorouracil resistance, respectively, and this is associated with changes in expression of the DNA-repair genes, MGMT and MLH1. In summary, our data suggest that RPL22L1 might be a prognostic marker in CRC and predict 5-FU responsiveness.